2021
DOI: 10.1016/j.ebiom.2021.103309
|View full text |Cite
|
Sign up to set email alerts
|

Burden of rare variants in synaptic genes in patients with severe tinnitus: An exome based extreme phenotype study

Abstract: Background tinnitus is a heterogeneous condition associated with audiological and/or mental disorders. Chronic, severe tinnitus is reported in 1% of the population and it shows a relevant heritability, according to twins, adoptees and familial aggregation studies. The genetic contribution to severe tinnitus is unknown since large genomic studies include individuals with self-reported tinnitus and large heterogeneity in the phenotype. The aim of this study was to identify genes for severe tinnitus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 48 publications
0
38
1
Order By: Relevance
“…Paired-end whole-genome sequencing involves sequencing both ends of a DNA fragment, which increases the likelihood of alignment to the reference and facilitates detection of genomic rearrangements, repetitive sequences, and gene fusions. Gene burden tests will be used to compare burden of loss of function SNV and structural variants in synaptic genes in patients with tinnitus, using Non-Finnish European dataset from gnomAD v3 as population database to estimate allelic frequencies [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Paired-end whole-genome sequencing involves sequencing both ends of a DNA fragment, which increases the likelihood of alignment to the reference and facilitates detection of genomic rearrangements, repetitive sequences, and gene fusions. Gene burden tests will be used to compare burden of loss of function SNV and structural variants in synaptic genes in patients with tinnitus, using Non-Finnish European dataset from gnomAD v3 as population database to estimate allelic frequencies [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exome sequencing of Spanish patients with Ménière’s disease and an extreme tinnitus phenotype uncovered 24 synaptic genes with an enrichment of rare missense variants [ 34 ]. A burden of rare variants in three candidate genes, ANK2 , TSC2 , and AKAP9 , was replicated in an independent Swedish cohort with severe tinnitus and was specific to the tinnitus phenotype through inclusion of data of patients with epilepsy who did not have tinnitus.…”
Section: Extreme Phenotype Approachmentioning
confidence: 99%
“…A burden of rare variants in three candidate genes, ANK2 , TSC2 , and AKAP9 , was replicated in an independent Swedish cohort with severe tinnitus and was specific to the tinnitus phenotype through inclusion of data of patients with epilepsy who did not have tinnitus. Gene-set enrichment analyses uncovered membrane trafficking and cytoskeletal binding in neurons [ 34 ]. This was the first study to link rare variants or large effect sizes to severe tinnitus and suggested genes associated with axonal branching and neuron connectivity in the brain.…”
Section: Extreme Phenotype Approachmentioning
confidence: 99%
“…The perceived impact of tinnitus can present a large interpersonal variability, and it can also vary over time. In addition, tinnitus can be considered as an annoying symptom in a small subgroup of patients [9]. There are no objective tests to determine the existence or severity of tinnitus, but there are many different standardized questionnaires to assess quality of life and annoyance related to tinnitus.…”
Section: Introductionmentioning
confidence: 99%